Lead poisoning in ancient Rome (2007)
Lead, a poisonous metal is extremely toxic even in microscopic quantities. The preponderance as well as the effectiveness of this greyish metal, especially in the production of domestic, industrial and architectural applications rendered it popular among ancient Romans. It was used for the production of pots, pans and cosmetics. It was also used for the production of water pipes, and enhancing the colour and taste of wine. A school of thought links lead poisoning to the fall of the ancient Roman Empire. On the other hand, another school of thought asserts that it is untenable to suggest that lead poisoning affecting the ruling aristocrats brought about the collapse of this great empire. However, both groups agree that lead poisoning was an issue in the empire. This discourse views the importance of lead; the role it played in the productivity of the empire and aspects of lead poisoning in ancient Rome